A Evolução Etimológica e Cultural do Termo "Dieta" - Falcato, Joana (2015)
The original meaning of the term "diet", which has its origin in the Greek term diaita, difers greatly from that assumed today. The return to its etymology and its initial cultural value enable greater understanding of what means, really, "being on a diet", a phrase which saw its meaning become impoverished, to be used commonly to mean "lose weight." The return to their origin enables simultaneously the understanding of the symbolic richness of the term and, from it, redefining the way in which can be understood and made known by health professionals.